An exploratory study to assess the acceptance and attitude towards COVID-19 vaccination among school-going adolescents aged 15-17 years in selected schools of Nadia district - Bhowmick, Saswati; Dhankher, Ruby; Mukhopadhyay, Ananya; Ahamed, Farhad; T., Latha; Rani, Jamuna; Joshi, Poonam (International Journal Of Community Medicine And Public Health, 2022)
The vaccination along with COVID appropriate behaviour plays a key role to decrease the spread of infection in all age groups. The present study aimed at assessing the acceptance and attitude of school-going adolescents aged between15-17 years who recently became eligible to be part of the COVID-19 mass vaccination drive in India along with matching up the COVID appropriate behaviour. A cross-sectional survey-based study was conducted in February 2022 among 300 school-going adolescents aged between 15-17 years selected through multi-stage sampling. A self-reported questionnaire survey instrument in the Google form was used to collect the data. A total of 260 adolescents responded with a response rate of 86.7%. Most of the participants were female (64.2%). The majority of adolescents (80%) had already taken the COVID-19 vaccination at the time of the survey. Very few adolescents had doubts regarding the safety of the vaccine (0.7%). Around 74.6% of adolescents had a good attitude towards COVID-19 vaccination with a mean score of 20.6±2.4. More than half of the adolescents (58%) reported good practice related to COVID appropriate behaviour (CAB) with a mean score of 48.2±6.2. The majority of school-going adolescents had a good attitude and acceptance towards the ongoing vaccination drive and reportedly observed good CAB practices. Long-term COVID-19 preventive approaches along with vaccination need to be employed to support the wellbeing of adolescents.